Arginine vasopressin modulates electrical activity and calcium homeostasis in pulmonary vein cardiomyocytes - Jen-Hung Huang (Journal of Biomedical Science, 2019)
Abstract Background Atrial fibrillation (AF) frequently coexists with congestive heart failure (HF) and arginine vasopressin (AVP) V1 receptor antagonists are used to treat hyponatremia in HF. However, the role of AVP in HF-induced AF still remains unclear. Pulmonary veins (PVs) are central in the genesis of AF. The purpose of this study was to determine if AVP is directly involved in the regulation of PV electrophysiological properties and calcium (Ca2+) homeostasis as well as the identification of the underlying mechanisms. Methods Patch clamp, confocal microscopy with Fluo-3 fluorescence, and Western blot analyses were used to evaluate the electrophysiological characteristics, Ca2+ homeostasis, and Ca2+ regulatory proteins in isolated rabbit single PV cardiomyocytes incubated with and without AVP (1 μM), OPC 21268 (0.1 μM, AVP V1 antagonist), or OPC 41061 (10 nM, AVP V2 antagonist) for 4–6 h. Results AVP (0.1 and 1 μM)-treated PV cardiomyocytes had a faster beating rate (108 to 152%) than the control cells. AVP (1 μM) treated PV cardiomyocytes had higher late sodium (Na+) and Na+/Ca2+ exchanger (NCX) currents than control PV cardiomyocytes. AVP (1 μM) treated PV cardiomyocytes had smaller Ca2+ i transients, and sarcoplasmic reticulum (SR) Ca2+ content as well as higher Ca2+ leak. However, combined AVP (1 μM) and OPC 21268 (0.1 μM) treated PV cardiomyocytes had a slower PV beating rate, larger Ca2+ i transients and SR Ca2+ content, smaller late Na+ and NCX currents than AVP (1 μM)-treated PV cardiomyocytes. Western blot experiments showed that AVP (1 μM) treated PV cardiomyocytes had higher expression of NCX and p-CaMKII, and a higher ratio of p-CaMKII/CaMKII. Conclusions AVP increases PV arrhythmogenesis with dysregulated Ca2+ homeostasis through vasopressin V1 signaling.